(untitled) (Anclajes, 2021)
I trace the arrival of José Lezama Lima’s novel Paradiso (1966) to Spain, the authorized Spanish edition appearing in 1976. To this end, I investigate the network of the Peninsula’s cultural actors who participated in its publication, using mainly correspondence between the Cuban writer and editors and Francoist censorship files housed in the General Archive of the Administration of the Ministry of Education, Culture and Sports in Alcalá de Henares.